The effect of applying governance mechanisms on and improving the quality of accounting information in Banks operating in Jordan from the employees point of view - Tarbeh, Ala’a Hashem Saleh (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to clarify the impact of applying the governance mechanisms on improving the quality of accounting information in banks operating in Jordan by applied a questionnaire to a sample of 316 workers in the Jordanian banks, and it reached the below results: (first): The percentage of applying governance mechanisms. and The percentage of applying The level of accounting information quality in banks operating in Jordan was good. (second): The effect of applying governance mechanisms on the quality of accounting information is positive and has a statistical indication, which indicates an increase and an improvement in the level of the accounting information quality due to the impact of applying governance mechanisms, and all that is from the point of view of employees in the study sample banks. (fifth): There is an effect of the interaction of educational qualification and experience of the workers in improving the quality of accounting information. And the higher the educational qualification and experience of the employees, the greater is the accounting information quality will be better. And The study presented proposals, and the most important one is to have an integrated framework for institutional governance that will contribute to spreading the culture of governance and its implementation in the banks and emphasizing the importance of working to increase the level of the accounting information issued, the high quality that contributes in strengthening the status of the institution and encouraging investments in it.